Efectos del uso de las principales fitohormonas aplicadas al cultivo de melón (Cucumis melo) en el Ecuador - Coloma Aguilar, Jonathan Mayer (2022)
Agriculture is considered one of the most important activities of the human being, it provides natural wealth as a source of vital importance for food security that is increasing and therefore different agricultural inputs have been used, among them growth regulators, the same, which are related to the growth and development of plants. Plant hormones or phytohormones are a compound produced inside plants that perform their function at very low concentrations, their main action being at the cellular level, changing the growth patterns of plants and allowing them to be controlled. These plant regulators are chemically synthesized compounds. or derived from other organisms, often much more powerful than their natural counterparts. It is necessary to take into account critical aspects such as application opportunity, dose, variety sensitivity, final plant condition, since each plant will require specific growth conditions that can be affected by their concentration in the medium, the Plant regulators are synthetic products that have become the first tools capable of controlling the growth and biochemical activity of plants, which is why their use has increased in recent years. This information can be used by various agricultural researchers, for potential applications in new crops, within this context, this review seeks to systematize the information on the discovery, synthesis and practical use of growth regulators in agriculture